Antimicrobial activityof seed extracts of Foeniculum vulgare on diarrhea causing bacteria - Abdul-Imam Almazini , Muna (University of Thi-Qar Journal of Science, 2012)
The antibacterial activity of ethanolic extracts from the seeds of Foeniculum vulgare was tested against Staphylococcus aureus, Escherichia coli, Salmonella enterica enterica (Typhi), Salmonella enterica enterica (Typhimurium) and Shigella dysenteriae pathogenic bacteria that cause diarrhea. The Minimum Inhibitory Concentration of the seed extract against Staphylococcus aureus and Escherichia coli is 300 mg /ml while that of Salmonella enterica enterica (Typhi), Salmonella enterica enterica (Typhimurium) and Shigella dysenteriae is 400 mg /ml, 500mg /ml and 600mg /ml respectively.